043. Multidiciplinary Management of Toxic Megacolon in Ulcerative Colitis: A Case Report and Review of Current Practice - Kurnianda, Ridho; Suswita, Rini; Setiawati, Yessy (JBN (Jurnal Bedah Nasional), 2024)
Background : Toxic megacolon is a life-threatening condition characterized by extreme colonic dilation and systemic toxicity. It often results from underlying inflammatory bowel disease, such as ulcerative colitis, or infectious colitis. Early recognition and management are crucial to prevent complications such as colonic perforation or sepsis.   Case : We present the case of a 42-year-old male with a history of ulcerative colitis based on histopathology examination who developed toxic megacolon. The patient presented with severe abdominal pain, distension, fever, and signs of systemic toxicity. Imaging studies revealed marked colonic dilation, and laboratory tests indicated elevated inflammatory markers. Initial management included broad-spectrum antibiotics, intravenous corticosteroids, and fluid resuscitation. Despite aggressive medical treatment, the patient’s condition worsened, necessitating surgical intervention. A total colectomy with ileostomy was performed, and the patient’s postoperative course was uncomplicated. Conclusion: This case underscores the importance of early diagnosis and intervention in toxic megacolon. A multidisciplinary approach involving gastroenterologists, surgeons, and intensivists is essential for optimizing patient outcomes. Future research should focus on improving early diagnostic markers and treatment protocols to better manage this critical condition.